Analysis of the Epitope Structure of Plum pox virus Coat Protein - Candresse, Thierry; Saenz, Pilar; Garcia, Juan Antonio; Boscia, Donato; Navratil, Milan; Gorris, María T.; Cambra, Mariano (2017)
Typing of the particular Plum pox virus (PPV) strain responsible in an outbreak has important practical implications and is frequently performed using strain-specific monoclonal antibodies (MAbs). Analysis in Western blots of the reactivity of 24 MAbs to a 112-amino-acid N-terminal fragment of the PPV coat protein (CP) expressed in Escherichia coli showed that 21 of the 24 MAbs recognized linear or denaturation-insensitive epitopes. A series of eight C-truncated CP fragments allowed the mapping of the epitopes recognized by the MAbs. In all, 14 of them reacted to the N-terminal hypervariable region, defining a minimum of six epitopes, while 7 reacted to the beginning of the core region, defining a minimum of three epitopes. Sequence comparisons allowed the more precise positioning of regions recognized by several MAbs, including those recognized by the 5B-IV1A universal MAb (amino acids 94 to 100) and by the 4DG5 and 4DG11 D serogroup-specific MAbs (amino acids 43 to 64). A similar approach coupled with infectious cDNA clone mutagenesis showed that a V74T mutation in the N-terminus of the CP abolished the binding of the M serogroup-specific AL MAb. Taken together, these results provide a detailed positioning of the epitopes recognized by the most widely used PPV detection and typing MAbs.